2006
DOI: 10.1007/s11095-006-9092-4
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Injectable Emulsions: Pharmacopeial and Safety Issues

Abstract: Lipid injectable emulsions have been routinely used in patients worldwide for over 40 years as a nutritional supplement in patients requiring parenteral nutrition. They can be given as a separate infusion or added into total parenteral nutrition admixtures. Despite such broad use, no pharmacopeial standards exist with respect to the optimal pharmaceutical characteristics of the formulation. Several attempts to establish standard physical and chemical attributes have been attempted by various pharmacopeias arou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
123
1
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(132 citation statements)
references
References 28 publications
3
123
1
4
Order By: Relevance
“…It is unclear what factors contribute to the degree of laboratory interference, but it is possible that infusion of multiple or large doses of ILE could result in decreased ILE clearance and increased serum persistence, leading to prolonged laboratory interferences. Lipid emulsions are often classified by their mean droplet size (MDS); in general, intravenous lipid emulsion (ILE) formulations have a MDS less than 1.0 μm [13]. These formulations are typically metabolized by lipoprotein lipase found along the vascular endothelium, while larger lipid formulations (MDS greater than 1.0 μm) are metabolized by reticuloendothelial system (RES) macrophages found in the microvasculature of the l u n g s , l i v e r, s p l e e n , a n d b o n e m a r r o w [ 1 3 ] .…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear what factors contribute to the degree of laboratory interference, but it is possible that infusion of multiple or large doses of ILE could result in decreased ILE clearance and increased serum persistence, leading to prolonged laboratory interferences. Lipid emulsions are often classified by their mean droplet size (MDS); in general, intravenous lipid emulsion (ILE) formulations have a MDS less than 1.0 μm [13]. These formulations are typically metabolized by lipoprotein lipase found along the vascular endothelium, while larger lipid formulations (MDS greater than 1.0 μm) are metabolized by reticuloendothelial system (RES) macrophages found in the microvasculature of the l u n g s , l i v e r, s p l e e n , a n d b o n e m a r r o w [ 1 3 ] .…”
Section: Discussionmentioning
confidence: 99%
“…Improving the poor solubility of this drug for delivery into target organs is an important issue which is one of the key points in the development of pharmaceutics. 13) We characterized the drug delivery carriers and determined the feasibility of nanoparticles for delivering tryptanthrin. We found that tryptanthrin-loaded SLNs, NLCs, and LEs overcame the insolubility problem, and allowed tryptanthrin to successfully penetrate breast cancer cells, especially when using the NLC system.…”
Section: Discussionmentioning
confidence: 99%
“…The phagocytosis process produces reactive oxygen species, the liver being the principal organ injured in this process. 52 Shortly after commencement of infusion of an unstable lipid emulsion, a pyrogenic response typified by fever, chest pain and signs of an anaphylactic-type reaction can manifest. This type of reaction is rare nowadays due to improved manufacturing processes.…”
Section: Safety Considerations Regarding Lipid Emulsion Administrationmentioning
confidence: 99%
“…60 In addition, allergic reactions, thrombophlebitis, muscle weakness, seizures in children, increased intracranial pressure after traumatic head injury, warfarin resistance (because lipids facilitate the anticoagulant binding to albumin), and impaired immune, reticuloendothelial and inflammatory responses have all been reported. 47,52 Availability of lipid emulsions in southern Africa Intralipid ® (Fresenius Kabi, South Africa) is available as a 20% solution and is packaged in 100 ml and 500 ml bags. It has a shelf life of 18 months from the date of manufacture.…”
Section: Notesmentioning
confidence: 99%